Kegiatan Pengabdian Masyarakat Terhadap Deteksi Dini Gangguan Perilaku, Emosional, Dan Psikososial Di Sekolah Dasar Negeri 02 Ciherang - Fransisca Iriani R Dewi; Divyas Bharath; Dany Setiawan; Nathanael Gumarus; Arya Dwi Saputra; Kacen Kacen; Yuri Prisiani; Alexander Halim Santoso (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Children and young people often face significant mental health challenges, which impact their emotional well-being and behavior. Our study aims to detect early signs of this problem in elementary school children using the Pediatric Symptom Checklist (PSC-17) questionnaire. It is hoped that it can increase the understanding of students and students to prevent the negative impacts of behavioral, emotional and psychosocial disorders.